ANALISIS KEAKSARAAN FUNGSIONAL MASYARAKAT PENGRAJIN ULOS DALAM MENDUKUNG KESEJAHTERAAN KELUARGA DI DESA WISATA BUDAYA - Jubaidah Hasibuan; Cindi Kezia Simbolon; Intan Yudha Prastika; Kaniwa Silvyani; Jeta Amina Siahaan; Wahyu Nur Ihsan; Ester Mega Rani Br Sinuhaji; Adis Adela Putri; Sonya Febiola Br Nadeak; Agnes Ginting (Jurnal Keluarga Sehat Sejahtera, 2025)
This study analyzes the literacy level of the community in Ulos Hamlet, Tanjung Rejo Village, as a basis for developing empowerment and functional literacy programs to support the potential of cultural tourism villages. Using a descriptive qualitative approach through participatory observation, focus group discussions, interviews using a checklist, and documentation studies, 22 informants were obtained purposively. The results show that no residents are at the basic literacy level. Four people are at the advanced literacy level with the ability to understand simple texts but are not yet consistent in their application. The majority (18 people) have achieved functional literacy, as seen from the application of literacy in economic activities such as the ulos weaving business, recording transactions, using cell phones, and simple digital promotion. These findings emphasize the need to strengthen digital literacy and business management to support the welfare and development of tourism villages.